Aktivitas Antibakteri Ekstrak Etanol Daun Cayratia trifolia L. Domin. Terhadap Bakteri Escherichia coli - Muhammad Ilyas; Sri Susanti; Karmilah Karmilah; Indriyani Pratiwi Hapsari (Halu Oleo University, 2018)
ABSTRACTPlant Cayratia trifolia L. Domin is one of the plants that can be used as a traditional medicine. One of them is the treatment of infectious diseases. Infectious diseases are the most disease suffered by the population in developing countries, including Indonesia. Some infectious diseases that can be caused by the bacterium Escherichia coli is a urinary tract infection or urinary tractus infection, diarrhea, prevalence of diarrheal diseases in Southeast Sulawesi Province was 7,3% higher than the national prevalence of diarrhea is 3,5 % this study aims to determine the antibacterial activity of ethanol extract of leaves C. trifolia L. Domin against the bacteria E. coli. This type of research is experimental research design using cylinder cup consisting of 5 treatments. Each treatment consists of three repetitions. C. trifolia L. Domin leaves then C. trifolia L. Domin as test materials made concentration of 10%, 20% and 30%. The results showed that ethanol extracts of leaves C. trifolia L. Domin with a concentration of 10% has an average value of 7,67 mm zone of inhibition concentration of 20% has an average value of 10,33 mm zone of inhibition and concentration of 30% has an average value 14,00 mm zone of inhibition. Results of ANOVA showed ethanol extract of leaves C. trifolia L. Domin had a zone of inhibition against Escherichia coli with different concentrations. And on the LSD (Least Significant Difference) concentration that was 30% effective in inhibiting the growth of bacteria E. coli. Keywords: zone inhibition, leaves Cayratia trifolia L. Domin, Escherichia coli, Cylinder cup.